Penyajian laporan keuangan entitas berorientasi nonlaba berdasarkan ISAK Nomor 35 pada Yayasan Panti Asuhan “Pononiungan” Bolaang Mongondow - Malasai, Firginia; Elim, Inggriani; Kalalo , Meily Y. B. (Yayasan Widyantara Nawasena Raharja, 2024)
A non-profit entity is one that is engaged in community service and has no intention of seeking profit. Non-profit entities obtain their funds from donors or contributors who do not expect a return on their investment. It is crucial that non-profit entities be held accountable, particularly in light of the growing number of foundations and community organisations. Funders and the community must be provided with clear financial reports that explain the entity's performance and resources. This study will determine the presentation of financial statements of non-profit entities based on ISAK 35 at the Pononiungan Orphanage Foundation in Bolaang Mongondow. This thesis employs a descriptive qualitative analysis method. The results are clear: the Pononiungan Orphanage Foundation in Bolaang Mongondow has adjusted its financial statements to align with the ISAK Number 35 standard. This comprises comprehensive income statements, cash flow statements, net asset change statements, and notes to the financial statements.